The Gas and Stellar Content of a Metal-poor Galaxy at z = 8.496 as Revealed by JWST and ALMA - K. E. Heintz; C. Giménez-Arteaga; S. Fujimoto; G. Brammer; D. Espada; S. Gillman; J. González-López; T. R. Greve; Y. Harikane; B. Hatsukade; K. K. Knudsen; A. M. Koekemoer; et al. (The Astrophysical Journal Letters, 2023)
We present a joint analysis of the galaxy S04590 at z = 8.496 based on NIRSpec, NIRCam, and NIRISS observations obtained as part of the Early Release Observations program of the James Webb Space Telescope (JWST) and the far-infrared [C ii ] 158 μ m emission line detected by dedicated Atacama Large Millimeter/submillimeter Array (ALMA) observations. We determine the physical properties of S04590 from modeling of the spectral energy distribution (SED) and through the redshifted optical nebular emission lines detected with JWST/NIRSpec. The best-fit SED model reveals a low-mass ( M _⋆ = 10 ^7.2 –10 ^8 M _⊙ ) galaxy with a low oxygen abundance of $12+log({\rm{O}}/{\rm{H}})={7.16}_{-0.12}^{+0.10}$ derived from the strong nebular and auroral emission lines. Assuming that [C ii ] effectively traces the interstellar medium, we estimate the total gas mass of the galaxy to be M _gas = (8.0 ± 4.0) × 10 ^8 M _⊙ based on the luminosity and spatial extent of [C ii ]. This yields an exceptionally high gas fraction, f _gas = M _gas /( M _gas + M _⋆ ) ≳ 90%, though one still consistent with the range expected for low metallicity. We further derive the metal mass of the galaxy based on the gas mass and gas-phase metallicity, which we find to be consistent with the expected metal production from Type II supernovae. Finally, we make the first constraints on the dust-to-gas (DTG) and dust-to-metal (DTM) ratios of galaxies in the epoch of reionization at z ≳ 6, showing overall low mass ratios of logDTG < −3.8 and logDTM < −0.5, though they are consistent with established scaling relations and in particular with those of the local metal-poor galaxy I Zwicky 18. Our analysis highlights the synergy between ALMA and JWST in characterizing the gas, metal, and stellar content of the first generation of galaxies.